Métodos de medição da altura e do volume comercial de árvores no bioma amazônico - Silva, Janiel Cerqueira da (2016)
This work aimed to evaluate different methods of measuring of height and merchantable volume of trees for sustainable forest management purposes in a native forest in the Amazon region. For this, the merchantable height measurement methods were analyzed: Visual with experienced; Suunto clinometer; Electronic hypsometer Haglöf II; Hypsometer Vertex IV and measurement with tree felled with the aid of a measuring tape. For obtaining the merchantable volume, the methods analyzed were scaling with Criterion RD 1000; estimation with the form factor of 0.7 considering in the calculating the cylinder volume the diameter at 1.30m and the measure visual experienced of the merchantable height; estimation with the form factor of 0.7 considering in the calculating the cylinder volume the diameter at 1.30m and merchantable height measured with the Suunto Clinometer and traditional cubing. Were measured 30 individuals of four species in a native forest located in the municipalities of Mâncio Lima and Rodrigues Alves, Acre. For analysis of the methods, the graphical analysis of residuals was performed, in addition to statistical bias (V), root mean square error (RMSE), average absolute differences (MD). Considering the merchantable height measurement methods, the Suunto stood out, being the most suitable for measuring the height of the trees in native forests in the Amazon. Among the methods of obtaining the merchantable volume with bark of trees, using the Criterion RD 1000 made it possible to obtain more accurate.